2006
DOI: 10.1016/j.intcom.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ‘Canned Communication’ for coordinating distributed mobile work activities

Abstract: Communication between physically distributed people in industrial and safety-critical domains is often spoken and mediated through walkie-talkies, or closed-circuit intercoms. Because this kind of communication is hampered by noise, radio interference, lack of persistency, etc. vital information is sometimes lost. In response to this challenge, this paper discusses the use of 'canned' text-based messaging as a supplement for improving such communication. Based on data from ethnographic studies of work activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Of the 23 papers reporting from lab evaluations, 14 involved some kind of context simulation. These simulation studies range from high-fidelity setups such as the use of a ship simulator in [38], to experimental setups where the level of simulation is rather low. As an example of the latter, Holzinger et al report from a study where the real life environment of an ambulance officer is simulated by the participant sitting on a chair in an office holding the PDA in his hands without laying down the elbows [23].…”
Section: Lab Studiesmentioning
confidence: 99%
“…Of the 23 papers reporting from lab evaluations, 14 involved some kind of context simulation. These simulation studies range from high-fidelity setups such as the use of a ship simulator in [38], to experimental setups where the level of simulation is rather low. As an example of the latter, Holzinger et al report from a study where the real life environment of an ambulance officer is simulated by the participant sitting on a chair in an office holding the PDA in his hands without laying down the elbows [23].…”
Section: Lab Studiesmentioning
confidence: 99%
“…Similar techniques were employed in the design of the maritime communicator (Kjeldskov and Stage 2006). The combination of OOA&D and Wisdom has been described in methodological form (Nielsen et al, 2006).…”
Section: Object-oriented Designmentioning
confidence: 99%
“…Research has shown that in such settings, increased value can be gained from the use of mobile and networked computer systems. Examples count remotely controlled service robots for the elderly or disabled (Hüttenrauch and Norman, 2001), wastewater treatment process control (Nielsen and Søndergaard, 2000), early diagnosing in emergency ambulances (van den Anker and Lichtweld, 2000) and coordination of distributed work activities on board large container vessels (Kjeldskov and Stage, 2006). Designing mobile computer systems for industrial domains is, however, not trivial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation